A Taste for Sweetness: Exploring Sugar-Sweetened Beverages Preferences Among College Students - Rahmawati, Indana Tri; Nurnaningsih Herya Ulfah; Anggi Renawati; Bekti Nirmala Dewi; Yusnita Rachmania (Poltekkes Kemenkes Tanjung Karang, 2025)
The consumption of sugar-sweetened beverages (SSB) is increasingly common among university students, raising concerns about long-term metabolic risks. This study aimed to describe SSB consumption patterns among university students in Malang City. A descriptive cross-sectional survey was conducted in July–August 2024 using an online questionnaire distributed through voluntary sampling. A total of 382 students participated. Data collected included demographics and SSB consumption habits; body weight and height were self-reported with instructions to refer to recent measurements. Results showed that 73.8% of students consumed SSB, most often during the day, with packaged tea being the most preferred type. Taste (45.3%) and affordability (38.7%) were the main purchase reasons, and minimarkets were the most common place of purchase. Overall, SSB intake among students was high, highlighting the need for educational interventions to promote healthier beverage choices.